WEBER-CHRISTCHEN’S DISEASE (CLINICAL EXPERIENCE) - A. P. Rebrov; O V Inamova; L L Alexeyeva; I. F. Shergina (Научно-практическая ревматология, 2002)
The case of severe form of Weber-Christchen’s disease in 31 year old man is described. The difficulty of diagnosis for the fist half a year is stressed - until characteristic nodes in subcutaneous layer appears. The diagnosis is confirmed by the data of biopsy of the node which revealed typical multinuclear macrophages with foamy cytoplasm (lypophages). The peculiarity of this case if the resistance of the disease to the combined treatment by high doses of GCS, cyloloxics and Sandimmune.